Journalism Culture and Political Conflict: Mexican Journalists Reflect their Performance During 2006 Presidential Elections - Márquez Ramírez, Mireya (Derecom. Revista Internacional de Derecho de la Comunicación y de las Nuevas Tecnologías, 2024)
This paper examines Mexican journalists’ perceived roles, values, and practices that shape the reporting of political conflict, such as the 2006 presidential elections—one of the most critical moments in contemporary political history. It is argued that traditional journalistic values often expected in Western models of journalism such as impartiality, objectivity, factuality and editorial detachment, turn out to be crucially passive devices to collect political utterances and promote information overload, scandal and superficiality. Exploring the views and testimonies of 85 radio and print journalists from twenty-one news organisations based in Mexico City, the paper outlines a typology of the varying ways in which Mexican journalists interpret and negotiate their roles and performance in relation to political conflict, by signalling out contradictions and dichotomies entangled in the construction of their occupational values, principles and roles. The paper shows how Mexican journalists were in a position to reflect on their own coverage and assess the extent to which they facilitated debate, described and/or explained occurrences, animated or reflected on political conflict and reported on or actively engendered social polarisation. It is revealed that journalistic roles embraced by Mexican journalists are trapped in contesting terrains of ambiguity. Clashing opinions about what to do meant that crucial information concerning the 2006 electoral conflict was left out from the public dominion, radio presenters handled information with an important charge of ideological and partisan bias, and reporters faced restrictions either imposed by their media’s economic interests or by existing inertial practices of reporting and gathering of information.